Asymmetric warfare for entrepreneurs 120 lessons from Lawrence of Arabia - Hanratty, Luan (MX Pub., 2011)
Asymmetric Warfare for Entrepreneurs is a handbook of guerrilla strategies for business, marketing, leadership and organization, adapted from TE Lawrence s revolutionary philosophy of war, Seven Pillars of Wisdom: A Triumph.